Condition of Rumen Fermentation as Impacted by Supplementation of Fermented Rice Brand Using In Vitro Gas Production Technique - Zuratih Zuratih; SPS Budhi; Z Bachruddin (Indonesian Center for Animal Research and Development (ICARD), 2020)
Methane is one of the gases produced by ruminants during feed fermentation in the rumen. This experiment was aimed to investigate the production of monacolin K in rice bran fermented by Monascus purpureus mold and the influence of the supplementation of fermented rice bran using Monascus purpureus mold on elephant grass basal diet on fermentation products and methane production in an in vitro gas production method. The study consisted of two experiments. The first experiment analysis of monacolin K production in fermented rice bran using Monascus purpureus. Fermentation is done by the addition of Monascus purpureus at levels 0, 4, 8, and 12% (v/w) of substrate (rice bran) with 3 replications. Monacolin K in the substrate was analyzed using HPLC. The second experiment was the evaluation of supplementation of fermented rice bran to elephant grass basal diet using in vitro gas production. The treatment diet evaluated were Pennisetum purpureum (control), Pennisetum purpureum:rice bran (1:1 ratio), and Pennisetum purpureum:rice bran fermented. Each treatment was replicated 3 times. Results from the first experiment shows that rice bran with the highest monacolin K content was in rice bran fermented at 12% by Monascus purpureus. Result from the second experiment showed that supplementation of fermented rice bran to Pennisetum purpureum basal diet did not affect rumen ammonia concentration, VFA, protein microbial production, and dry matter and organic matter digestibility. However, methane production (CH4) was reduced (P<0.05) by 50%, and the protozoal population was decreased (P<0.05) by 80%. It is concluded that supplementation of fermented rice brands containing monacolin K was able to reduce methane production and the protozoa population without affecting feed fermentation.